2018
DOI: 10.3389/fimmu.2018.01818
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1–RIPK3–MLKL-Associated Necroptosis Drives Leishmania infantum Killing in Neutrophils

Abstract: Necroptosis is a pro-inflammatory cell death, which happens in the context of caspase-8 inhibition, allowing activation of the receptor interacting protein kinase 1–receptor interacting protein kinase 3–mixed lineage kinase domain-like (RIPK1–RIPK3–MLKL) axis. Recently, necroptosis has emerged as a key component of resistance against pathogens including infected macrophage by Leishmania infantum, the ethiologic agent of Visceral leishmaniasis (VL). VL is the most severe form of Leishmaniasis, characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Further studies are necessary to further investigate apoptosis induced by these species and cellular mechanisms involved in death. Notably L. infantum infected neutrophils were shown to undergo necroptosis in presence of specific caspase 8 inhibitor (and so when apoptosis was inhibited) (Barbosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are necessary to further investigate apoptosis induced by these species and cellular mechanisms involved in death. Notably L. infantum infected neutrophils were shown to undergo necroptosis in presence of specific caspase 8 inhibitor (and so when apoptosis was inhibited) (Barbosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, RIPK1, a death domain-containing Ser/Thr kinase, has an established role in mediating the deleterious mechanisms downstream of type I tumor necrosis factor α receptor (TNFR1) 10 . Activated RIPK1 and RIPK3 form the necrosome complex and then recruit MLKL, leading to necroptosis execution and mitochondrial membrane disintegration 11,12 . The involvement of necroptosis is reported in neurodegenerative diseases, including amyotrophic lateral sclerosis and Alzheimer’s disease 6,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, the effect of zVAD-mediated necroptosis in the regulation of inflammatory diseases has remained controversial and zVAD may play multiple roles in inflammatory diseases (21). Although many studies have shown that zVAD-mediated necroptosis contributes to the pathogenesis of inflammation, some other studies indicated that necroptosis plays an antiinflammatory role by preventing specific viral and bacterial infections, and could contribute to tissue generation (22,23). For example, zVAD showed positive effect on lung injury in the severe acute pancreatitis model (SAP) in rats, but had a negative effect in severe pneumovirus disease in mice (24,25).…”
Section: Introductionmentioning
confidence: 99%